Synoptic analysis of the hail wave and snowfall in Iraq in February 2020 - Abdul Rahman, Maisara Adnan (Al-Adab Journal, 2021)
The paper is an analysis of the cold wave and snowfall in Iraq which extended from 09/ 02/ 2020 to 13/ 02 / 2020. On the basis of the Iraqi meteorological data of snowfall, the stations of Mosul, Baghdad, Rutbah, Hilla, Kut and Karbala have been chosen for study. The findings show that there was a three- day snowfall in Mosul and one- day in the others and the lowest temperature was) -7°C (in Mosul and Baghdad; the temperature did not exceed) 2°C (. As for the atmospheric pressure, it ranged between medium and high values ​​(1019.9-1031.8) millibars. The wind speed values ​​ranged between (6 (-) 00) m / s. As for the prevailing trend, it was northeast; humidity reached high levels, ranging between 51-100%, and clouds covered the sky by 8-eighths most of the time. The snowfall was due to the control of a cold polar air mass represented by the Siberian Highland at the surface pressure level, and it was shallow, as an air depression was at 850 millibars and the temperatures ranged between-) 0° (and-) 5° (C. The main source of this cold wave was the control of the groove at the level of 500 millibars, as the temperature reached 25 degrees below zero in the central region of Iraq and(- 20°C) in southern Iraq in addition to the emergence of the axis of the polar jet stream accompanying the snowfall at a speed of up to 100 knots in central Iraq and it became clear from the analysis of these previous levels that there is a deep groove extending from 300 millibars to 850 millibars there was also a case of blocking which went from a pressure level of 300 millibars down to an surface pressure omega block and high – over – low types.